ANALISIS KINERJA PEGAWAI DALAM PELAYANAN PUBLIK PADA PROGRAM PASCASARJANA UNIVERSITAS CENDERAWASIH KOTA JAYAPURA PAPUA - Surdaningsih Surdaningsih; Yosephina Ohoiwutun (Universitas Cenderawasih, 2023)
This study aims to analyze the performance of employees in public services at the Cenderawasih University Postgraduate Program, as well as describe the determinant factors that influence the performance of Cenderawasih University Postgraduate Program employees. The research method used is descriptive qualitative. Research locations focused on the Cenderawasih University Postgraduate Program, with consideration of accessibility in conducting research. The informant determination technique was carried out purposively, for those who were considered to know the research problem. Then, the data collection techniques used were observation and interviews, then the research instruments included interview guides and recording devices. Data analysis techniques through the stages of data categorization, data description, and data interpretation. The results showed that the performance produced by employees in the Cenderawasih University postgraduate program was not optimal. This was seen from the quality of results, discipline, responsibility, target accuracy, and cooperation shown in carrying out public services. Lack of awareness and good coordination. Although the employees always try to maximize their work. Support for available facilities and also aspects of the quality of human resources. newer technology employees who are less solid or have difficulty working in teams. However, the problem or obstacle comes from employees who don't care enough, so they forget their responsibilities to work in a team.